An immediately post-Walras generation of mathematical economists - Centurião, Lúcia Regina (2022)
This thesis studies the history of mathematization of economics, in particular, the dissemination of the Walrasian general equilibrium theory at the beginning of the 20th century. Two main perspectives were used. I first analyzed this dissemination through the works of three authors who adopted Walrass ideas: Henry Ludwell Moore in the United States, and Albert Aupetit and Etienne Antonelli in France. The second perspective is´ the dissemination of Walrasian ideas in the classroom. For this, I investigated general treatises used for teaching at that time, which presented the Walrasian model. Believing that the lack of interest in Walrasian theory by young people was due to its lack of empirical content, Henry Moore, a professor at Columbia University, developed a version of the Walrasian model that could be empirically tested. Albert Aupetit, for his part, also believed in the important role that statistics could play in the theory; however, his main concern was with the monetary aspect of Walrass model. Etienne Antonelli was inter-´ ested in Walrass ideas about using mathematics in economics and about the cooperative movement. Both Aupetit and Antonelli failed twice in the selection process to become professors in France, and devoted themselves to other activities outside the academy: Aupetit became secretary general of the Bank of France and Antonelli became a French politician, responsible for the law that established the social security system in France in 1928. The work shows, therefore, how the institution of the concours dagr´egation may have made it difficult for the Walrasian general equilibrium theory to be taught in France. The thesis also shows that probably some of Walrass main followers in France at the beginning of the 20th century were in policy-making, and outside the academy. In the three first chapters one theme is central: Walrass Abrégé, the version of his theory developed for the classroom, written for Aupetit to use in France with no success, since Aupetit failed the concours dagr´egation. The thesis also shows how Walras tried to get a translation of the work by Moore, without success too. Finally, after Walrass death in 1910, Antonelli published the Abrégé in 1914, with some modifications. However, the general equilibrium theory became famous with the publication of two books: Cassel (1924) and Bowley (1924), which presented the model without attributing authorship to Walras. In the fourth chapter I analyzed three books Cassel (1924), Bowley (1924) and Antonelli (1914). The chapter concluded that, regarding the dissemination of the Walrasian general equilibrium theory, although the three books presented Walrass framework, they also presented at the same time antagonistic fundamental beliefs about what was economic science and its scope. Therefore, Walrass model was taught in very different theoretical frameworks: no one dominant group appropriated it.